Medical Student Radiology Education: Summary and Recommendations From a National Survey of Medical School and Radiology Department Leadership - Straus, Christopher M.; Webb, Emily M.; Kondo, Kimi L.; Phillips, Andrew W.; Naeger, David M.; Carrico, Caroline W.; Herring, William; Neutze, Janet A.; Haines, G. Rebecca; Dodd, Gerald D. (Journal of the American College of Radiology, 2014)
The ACR Task Force on Medical Student Education in Radiology, in partnership with the Alliance of Medical Student Educators in Radiology, investigated the current status of how and to what extent medical imaging was being taught in medical schools. The task force executed a 3-part survey of medical school deans, radiology department chairs, and intern physicians. The results provided an updated understanding of the status of radiology education in medical schools in the United States. This summary includes recommendations about how individual radiology departments and ACR members can assist in advancing the specialty of diagnostic radiology through medical student education.